1999
DOI: 10.1007/s004050050120
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preoperative tracheotomy on T3 transglottic carcinomas of the larynx

Abstract: To evaluate the impact of the practice of a preoperative tracheotomy and different prognostic factors reported in the literature in patients with transglottic carcinoma of the larynx, a retrospective study was performed in the Instituto Nacional de Cancerologia, Mexico City. In all, 90 cases with T3 transglottic squamous cell carcinoma requiring a total laryngectomy as primary treatment were studied. Prognostic factors such as the Karnofsky index, tumor differentiation, surgical margins and preoperative trache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 27 publications
1
19
2
Order By: Relevance
“…Several studies have shown poor outcome of patients with tracheotomy. 18 The dismal survival of patients with tracheotomy in this series is consistent with literature and tracheotomy emerged as the only independent prognostic factor significantly associated with poor LFS on multivariate analysis. The potential risk of prolongation of radiotherapy treatment time in head and neck is well documented.…”
supporting
confidence: 89%
“…Several studies have shown poor outcome of patients with tracheotomy. 18 The dismal survival of patients with tracheotomy in this series is consistent with literature and tracheotomy emerged as the only independent prognostic factor significantly associated with poor LFS on multivariate analysis. The potential risk of prolongation of radiotherapy treatment time in head and neck is well documented.…”
supporting
confidence: 89%
“…CR to chemoradiation has already been reported as an important prognostic factor for overall survival in previous studies including different chemoradiation protocols [14] . Carrilo et al [15] retrospectively studied the negative impact of preoperative tracheotomy in T3 transglottic tumors submitted to total laryngectomy. Ninety cases were studied, and 32 needed a preoperative tracheotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this information, some authors recommend an immediate total laryngectomy instead of an emergency tracheotomy [15][16][17] . During follow-up, only 2 patients with tracheotomy had stomal relapses; most relapses were loco-regional, independent of tracheotomy status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The local control rate is poorer even when the patients undergo laryngectomy. Tracheostomy has been associated with inferior duration of OS and increased rate of distant metastasis in some series [46]. …”
Section: Introductionmentioning
confidence: 99%